The Effect of Work Motivation and Compensation on Employee Work Productivity at PT Kereta Api (Persero) Divre III Palembang - Depiansah, Dendi; Mellita, Dina (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine and analyze the effect of motivation and compensation on employee productivity at PT. Kereta Api (Persero) Divre III Palembang by distributing questionnaires to 150 respondents. The technique used in this study is a questionnaire technique with saturated sampling method. The variables studied are productivity as the dependent variable while motivation and compensation are the independent variables. The analysis technique used is Partial Least Square Structural Equation Modeling (PLS SEM) using the Smart Pls application. From the results it was recorded that the variables of motivation and compensation have a direct significant effect on employee work productivity. The significant influence of these variables can be seen from the results of Cross Loading that the value of Factor Loading when associated with other latent variables has the best discriminant validity. For motivation and compensation variables on productivity it is stated that it is influential or reliable.